The Effect of Biochar and N-P-K Fertilizer Formulation on Soil Chemical Properties and Coffee Plant Growth - Hanifa, Hana; Maryanto, Joko; Irmawan, Roma (ENVIBILITY: Journal of Environmental and Sustainability Studies, 2025)
Indonesia has abundant natural resources as potential capital for developing coffee commodities. This research aims to determine the effect of applying biochar and N-P-K fertilizer at different doses on soil chemical properties and growth in coffee plants. This research was carried out on the land of Sikapat Village. Sumbang District, Banyumas Regency. Analysis of soil quinua properties was carried out at the Laboratory, Faculty of Agriculture, Unsoed. This research was carried out from September 2023 to February 2024. The method used was an experimental method with a two-factorial Randomized Block Design (RAK) with 3 replications. The factors tried in the research were biochar treatment (B0 = 0 g biochar, B1 = 100 g biochar, B2 = 150 g biochar) and N-P-K fertilizer treatment (P0 = without N-P-K fertilizer, P1 = N-P-K fertilizer 65 g (25 g N fertilizer, 20 g P fertilizer, and 20 g K fertilizer), P2 = N-P-K fertilizer 130 g (50 g N fertilizer, 40 g P fertilizer, and 40 g K fertilizer). The soil chemical property variable tested was pH H₂O. PH KCL, C-organic, N-total, P-total, K-total, and CEC. The observation data were analyzed using analysis of variance (ANOVA) and continued with the Duncan Multiple Range Test (DMRT) at a significant difference level of 5%. The research results showed that the administration of biochar and N-P-K fertilizer at different doses had a real effect on the pH H2O variable, pH KCl, N-total, P-total, plant height, and stem diameter. Meanwhile it had no effect significantly on variables C-organic, K-total, CEC, and K uptake.